2003
DOI: 10.1111/j.1572-0241.2003.07179.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms in patients infected with hepatitis B virus

Abstract: These findings suggest an association between the genetic ability to produce low levels of IFN-gamma and the susceptibility to develop chronic HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
128
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(130 citation statements)
references
References 35 publications
2
128
0
Order By: Relevance
“…Combined therapy with ribavirin and IFN-a for chronic hepatitis B not only significantly reduces viremia levels but also induces lasting CD4 + T cell proliferation and Th1 cytokine release at the site of infection [14]. It was also suggested that healthy individuals who recovered from HBV infection had a distribution of IFN-c gene polymorphism similar to healthy controls; however, the majority of the chronic patients exhibited the potential to produce low levels of IFN-c [2]. The e protein triggers a T cell-dependent immune response, while the core protein triggers both T cell-independent and T cell-dependent immune responses.…”
Section: Discussionmentioning
confidence: 96%
“…Combined therapy with ribavirin and IFN-a for chronic hepatitis B not only significantly reduces viremia levels but also induces lasting CD4 + T cell proliferation and Th1 cytokine release at the site of infection [14]. It was also suggested that healthy individuals who recovered from HBV infection had a distribution of IFN-c gene polymorphism similar to healthy controls; however, the majority of the chronic patients exhibited the potential to produce low levels of IFN-c [2]. The e protein triggers a T cell-dependent immune response, while the core protein triggers both T cell-independent and T cell-dependent immune responses.…”
Section: Discussionmentioning
confidence: 96%
“…Cytokines play a key role in the regulation of the immune response and the capacity of cytokine production differs among individuals and correlates with the polymorphism in the cytokine gene promoters (Ben-Ari et al, 2003). Host resistance to Brucella has been mainly studied in mice and shown that cytokines control the immune response and influence the outcome of the disease (Baldwin and Parent, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al (2006) demonstrated that the -592G/A variant affects HCC risk, while Qiu et al (2011) reported that certain genotypes of the -819 and -592 SNPs increase and decrease susceptibility, respectively. Furthermore, Truelove et al (2008) suggested that IL-10 gene sequence variations influence HBV infection outcome, although Ben-Ari et al (2003) reported that the polymorphisms investigated in the current study are not associated with development of chronic HBV infection and related diseases. Finally, Heneghan et al (2003) conducted a study among the Hong Kong Chinese population, finding that IL-10 polymorphisms do not contribute to HCC susceptibility.…”
Section: Discussionmentioning
confidence: 75%
“…Yang and Fa (2015) indicated that IL-10 -1082A/G constitutes a candidate biomarker for the prediction of susceptibility to esophageal cancer, while Vinod et al (2015) suggested that the AA genotype of this SNP correlates with breast cancer oncogenesis in the South Indian population. Several previous studies have examined the association between IL-10 gene polymorphisms and development of HCC (Ben-Ari et al, 2003;Heneghan et al, 2003;Tseng et al, 2006;Truelove et al, 2008;Qiu et al, 2011;Wei et al, 2011). Tseng et al (2006) demonstrated that the -592G/A variant affects HCC risk, while Qiu et al (2011) reported that certain genotypes of the -819 and -592 SNPs increase and decrease susceptibility, respectively.…”
Section: Discussionmentioning
confidence: 99%